2021
DOI: 10.1016/j.csbj.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous ionic liquids redistribute local enzyme stability via long-range perturbation pathways

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 119 publications
(210 reference statements)
3
28
0
Order By: Relevance
“…From the RMSF we find that, in general, the fluctuations of the individual amino acids are dampened with increasing ionic strength. This is consistent with previous protein-IL simulation studies that have shown that the addition of ILs reduces protein dynamics …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…From the RMSF we find that, in general, the fluctuations of the individual amino acids are dampened with increasing ionic strength. This is consistent with previous protein-IL simulation studies that have shown that the addition of ILs reduces protein dynamics …”
Section: Resultssupporting
confidence: 93%
“…This is consistent with previous protein-IL simulation studies that have shown that the addition of ILs reduces protein dynamics. 59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some negatively charging approaches emphasized that negative enzyme surfaces favorably diminish the attraction of anions. , Interestingly, our recent study revealed that the effects of cations and anions depend on their different combinations . In detail, BMIM + cations interacted more favorably with the BSLA surface in the case of halogenated-BMIM (i.e., [BMIM]­Cl, [BMIM]­Br, [BMIM]­I), whereas BMIM + cation interactions were almost equal with TfO – anions (in case of [BMIM]­[TfO]) on the BSLA surface. , In addition, we found that identifying the perturbation pathways from IL indirect effects and specific IL ion–residue interactions enable the effective prediction of focused variant libraries with enhanced IL resistance …”
Section: Introductionmentioning
confidence: 96%
“…11,34 In addition, we found that identifying the perturbation pathways from IL indirect effects and specific IL ion−residue interactions enable the effective prediction of focused variant libraries with enhanced IL resistance. 35 Collectively, charge engineering of enzymes and its implication on IL ions is complicated and is far from fully understood, which hamper the protein engineers' ability to modify the enzymatic activity and stability in ILs efficiently. Generally, the global design principles of enzymes are difficult to find in random mutagenesis libraries.…”
Section: ■ Introductionmentioning
confidence: 99%